Avian Provocation: Roosters and Rime Royal in Fifteenth-Century Fable. (2nd October 2017) - Chaganti, Seeta
Abstract: Despite the conservative programs of John Lydgate's and Robert Henryson's fifteenth-century retellings of the "cock and jewel" fable, these texts find ways to provoke both their own audiences and us as modern readers. This essay will demonstrate that the fable's provocations reveal themselves in the quotidian vocality of the medieval chicken yard. The soundscape of this space attunes the poetic audience to variations in the pace of rime royal, and this complex pacing draws out new meanings of the fabular moral. When read in terms of poultry sound, both Henryson and Lydgate's verses provoke readers to negotiate nuances of relation between individual experience and generalities of convention in formulating an understanding of value.